The explorer's roadmap to national-socialism : Sven Hedin, geography and the path to genocide - Danielsson, Sarah Kristina (Ashgate, 2012)
Introduction: at the heart of the matter: the politics of science -- Part I. From geographer to political activist, 1880-1933: Geographical knowledge is world power: Sven Hedin's rise to fame and influence, 1885-1903; the ideological conviction of a germanic nationalist: Hedin the agitator, 1904-1913; at the front lines of the great war: defending the Germanic cause, 1914-1918; "there is a cancer in the middle of Europe": Hedin's national-socialist blue-print, 1919-1934 -- Part II. The Nazi years and the aftermath, 1934-1952: The hour of retribution has struck: the fateful years, 1935-1938; on a mission in Berlin: plans for the East and the move towards genocide, 1939-1941; the truest friend of the Third Reich: justifying genocide, 1942-1945; the final years: Sven Hedin, Apologia pro vita sua -- Conclusion: the politics of science: in defense of the indefensible